Allelic and Genotype Frequencies of CYP2B6∗2 (64C > T) and CYP2B6∗3 (777C > A) in Three Dominant Ethnicities of the Iranian Population. (9th February 2023) - Khavandegar, Armin; Tavakoli-Far, Bahareh; Ansari, Sarina; Veis-Karami, Parisa; Ghasemi, Faezeh; Sheibaninia, Samira; Jazayeri, Roshanak; Houshmand, Massoud
Abstract : Background . Cytochrome P450 complex plays a key role in drug metabolism. CYP2B6 has an essential part in Cytochrome P450 complex metabolism. This study aims to determine the allelic distribution of CYP2B6 ∗ 2 and CYP2B6 ∗ 3 in three main Iranian ethnicities: Fars, Turk, and Kurd. Methods . The study was conducted on 174 unrelated healthy volunteers from three main Iranian ethnicities. After DNA extraction from peripheral blood samples, genotyping of CYP2B6 ∗ 2 and ∗ 3 was performed using tetra ARMS and ARMS PCR, respectively. Results . The average age of 174 cases was 40.69 ± 11.87 (mean ± SD) and 39.06 ± 11.63 (mean ± SD) for males and females. In the CYP2B6 ∗ 2 variant, the genotyping frequency of wild type (C/C), heterozygous (C/T), and homozygous mutant (T/T) was 8.7%, 86%, and 5.2%, respectively. The CYP2B6 ∗ 2 (c.64C > T) allele frequency was 48.2% (95% CI: (37.8–58.6)). In the CYP2B6 ∗ 3 variant, the frequency of wild type (C/C), heterozygous (C/T), and homozygous mutant (T/T) was 75.3%, 11%, and 13.6%, respectively. The CYP2B6 ∗ 3 (c.777C > A) allelic frequency was 19.1% (95% CI: (17.5–20.7)). Conclusion . Allelic distribution in three main Iranian ethnicities, i.e., Turk, Kurd, and Fars, is remarkably higher than that in other populations, even that in Southern Iran. High frequencies of CYP2B6 ∗ 2 and ∗ 3 in the Iranian population highly affect drug responsiveness. Understanding such variability could help to increase drug efficacy and reduce its toxicity.